2020
DOI: 10.1021/acsaelm.0c00728
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Based Self-Healing Cu(II)-Metallohydrogels: Efficient Third-Order Nonlinear Optical Materials in Terms of an Intensity-Dependent Refractive Index and Two-Photon Absorption

Abstract: Two protein-based self-healing Cu(II)-metallohydrogels named BSA-CuA and BSA-CuCl have been synthesized by mixing acetate and chloride salts of Cu(II) distinctly with the protein bovine serum albumin (BSA) in water medium. Experimentally investigated rheological parameters of both synthesized metallohydrogels not only expose the viscoelastic semi solid nature and mechanical toughness but also reveal the self-healing properties of both metallohydrogel materials. Counteranion-directed morphological variations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…The porous nanomaterial sintered body has strong activity and is suitable for catalysts and high-power capacitors. If the particle size of nanocrystalline material becomes smaller, its volume fraction will increase [8]. Generally speaking, the internal structure of nanocrystals consists of two different types of atoms.…”
Section: Crystalline Nanooptical Materials and Motionmentioning
confidence: 99%
“…The porous nanomaterial sintered body has strong activity and is suitable for catalysts and high-power capacitors. If the particle size of nanocrystalline material becomes smaller, its volume fraction will increase [8]. Generally speaking, the internal structure of nanocrystals consists of two different types of atoms.…”
Section: Crystalline Nanooptical Materials and Motionmentioning
confidence: 99%
“…Till now, countless metallogels have been synthesized using different transition metal ions including Co(II), [44][45][46] Ni(II), 47,48 Cu(II), 47,48 Cd(II), 49,50 Fe(II/III), [51][52][53] Zn(II), 48,54 and Mn(II) 25 for different application purposes. 2,55 Copper based metallogels have numerous applications like redox activity, 56 proton conductivity, 57 self-healing property, 58,59 catalysis, 60 superconductor, 61 and harmful organophosphate sensing. 62 Currently, researchers are continuously trying to discover new functional materials for energy related applications to meet the worldwide energy demand with energy storage devices, 63,64 energy conversion devices, 65 solar cells, 66,67 low-friction materials, 68,69 corrosiveresistant coating, 70,71 organic photovoltaic devices, [72][73][74][75] photodetectors, 76,77 fuel cells, 78 water splitting, 79 thin-film solar cells, [80][81][82] light-emitting devices, 83 metal-organic gels t...…”
Section: Introductionmentioning
confidence: 99%
“…34 The OA data reveal reverse saturation absorption due to two photon absorption (TPA). The TPA coefficients ( β ) of Co-AA and Ni-AA are found to be (1.503 ± 0.045) × 10 −1 cm GW −1 and (1.381 ± 0.029) × 10 −1 cm GW −1 , which are one order of magnitude higher than our previously reported protein-based BSA@CuA metallhydrogel, 34 and also of the same order as a standard material like fullerene. 60 The estimated third-order nonlinear susceptibility is of the order of 10 −14 (esu).…”
Section: Introductionmentioning
confidence: 99%
“…Majumdar et al reported self-healing Cu(II)-metallohydrogels (BSA@CuA) based on bovine serum albumin protein using the pioneering approach of prominent and efficient third-order non-linear optical materials. 34 The polarity of different chemical constituents involved in the gelforming scaffolds is considered one important reason for executing self-healing behaviour. [35][36][37] Recent studies on synthesized nanocrystals and plasmonic nanostructures have reported them to be advanced materials for NLO studies 38,39 Significant studies on advanced nanomaterials are progressing these days due to their potential applications in photocatalytic activity, 40 optoelectronic data storage, 41 etc.…”
Section: Introductionmentioning
confidence: 99%